2021
DOI: 10.3389/fpsyt.2021.636513
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Internalized Transnegativity and Protective Factors With Depression, Anxiety, Non-suicidal Self-Injury and Suicidal Tendency in Trans Populations: A Systematic Review

Abstract: Discrimination heavily impacts the lives of trans populations and causes adverse mental health outcomes. As stated by the Gender Minority Stress Model self-stigmatization could play an important role in this process. The aim of this systematic review is to investigate whether there is a positive association between self-stigmatization and mental health and to identify mediation factors. Studies which quantitatively investigated the association between internalized transnegativity and selected mental health out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…We found that internalized transphobia was negatively associated with psychological well-being. This finding is consistent with findings in the literature [ 17 , 49 , 50 ], confirming that internalized transphobia is a significant risk factor for psychological well-being in TGNC populations. Specifically, this finding is particularly consistent with Hendricks and Testa’s [ 17 ] theories about the detrimental effects of internalized transphobia on the mental health of TGNC individuals, as well as internalized homophobia for the lesbian, gay, and bisexual population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that internalized transphobia was negatively associated with psychological well-being. This finding is consistent with findings in the literature [ 17 , 49 , 50 ], confirming that internalized transphobia is a significant risk factor for psychological well-being in TGNC populations. Specifically, this finding is particularly consistent with Hendricks and Testa’s [ 17 ] theories about the detrimental effects of internalized transphobia on the mental health of TGNC individuals, as well as internalized homophobia for the lesbian, gay, and bisexual population.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we highlighted that loneliness was a significant mediator between internalized transphobia and psychological well-being. This is the most innovative finding of the current study, as it sheds light on possible mediators of a relationship generally considered to be direct (i.e., internalized transphobia and health outcomes) [ 22 , 50 ]. Thus, we can assume that one of the reasons internalized transphobia increases the likelihood of developing negative mental health outcomes is because this proximal stressor creates the perception of being alone in a world that stigmatizes gender diversity, which likely also makes it difficult to benefit from the support of the TGNC community.…”
Section: Discussionmentioning
confidence: 99%
“…Some prior research has individually tested associations between internalized transphobia or negative expectations and mental health outcomes. Specifically, internalized transphobia has been demonstrated to relate to depression (Chodzen et al, 2019; Hidalgo et al, 2019; Inderbinen et al, 2021; Kolp et al, 2020; Testa et al, 2015; Timmins et al, 2017), general anxiety (Chodzen et al, 2019; Inderbinen et al, 2021; Kolp et al, 2020; Timmins et al, 2017), social anxiety (Hidalgo et al, 2019; Testa et al, 2015), and PTSD (Barr et al, 2022). Similarly, negative expectations have been demonstrated to relate to depression (Hidalgo et al, 2019; Testa et al, 2015; Timmins et al, 2017), general anxiety (Chodzen et al, 2019; Timmins et al, 2017), and social anxiety (Hidalgo et al, 2019; Testa et al, 2015); however, no studies have tested whether negative expectations are related to PTSD.…”
Section: The Gender Minority Stress Modelmentioning
confidence: 99%
“…Gender-diverse people experience substantial deleterious mental health outcomes in the United States (U.S.), including anxiety, depression, general psychological distress, and suicidality (Hunt et al, 2021; Inderbinen et al, 2021; James et al, 2016; Lefevor et al, 2019; Newcomb et al, 2020; Testa et al, 2017). This is due to systematic stigmatization from cisnormativity, or prevailing socially-constructed notions of gender and sex that enforce binary cisgender expectations and stigmatize those who violate the norms of their assigned sex (Baril & Trevenen, 2014).…”
Section: Present Investigationmentioning
confidence: 99%
“…Minority stress theory (Brooks, 1981; Hendricks & Testa, 2012; Meyer, 2003; Rood et al, 2016; Testa et al, 2015) is one of the prevailing theories in transgender health research, positing that those with stigmatized gender identities experience bias, stigma, and discrimination, which erode one’s mental health. In this line of research, distal (e.g., harassment, family rejection) and proximal (e.g., internalized transphobia and identity concealment) gender minority stressors have been associated with risk for general psychological distress, suicidal ideation, depression, and anxiety (Brennan et al, 2017; Chodzen et al, 2019; Inderbinen et al, 2021; Lefevor et al, 2019; Lloyd et al, 2019; Puckett et al, 2020; Tebbe & Moradi, 2016; Testa et al, 2015, 2017; Timmins et al, 2017). Although there is considerable evidence that minority stressors erode the mental health of transgender/nonbinary people, few studies have simultaneously examined multiple forms of distal minority stress and their impact on psychological distress among gender minority people.…”
Section: Present Investigationmentioning
confidence: 99%